INTEGRATIVE COURSES AS A METHODOLOGICAL FOUNDATION IN THE SYSTEM OF CONTINUOUS EDUCATION OF THE TWENTY-FIRST CENTURY - Luzik, E.V.; Akmaldinova, O.M. (Proceedings of National Aviation University (archive), 2005)
Considered are the theoretical and methodological bases for the development of integrative courses as a holistic process of shaping specialists, both personally and professionally, that puts in place the conditions necessary for developing further their creative personality; with a level of creative potential marking all the stages of activity of the person, that retains his / her creative essence – the tendency to search and transform.